Whole-Genome Sequencing and De Novo Assembly of Malassezia pachydermatis Isolated from the Ear Canal of a Dog with Otitis - D’Andreano, S. (Microbiol Resour Announc, 2021)
We have de novo assembled the genome sequence of Malassezia pachydermatis isolated from a canine otitis sample with Nanopore-only long reads. With 99× coverage and 8.23 Mbp, the genome sequence was assembled in 10 contigs, with 6 of them corresponding to chromosomes, improving the scaffolding of previous genome assemblies for the species.